Corpus linguistics and textual history: a computer-assisted interdisciplinary approach to the Peshiṭta - Keulen, P. S. F. van; Peursen, W. Th. van (Studia Semitica Neerlandica, 2006)
Preliminary Material /P.S.F. van Keulen and W.Th. van Peursen -- Introduction /Wida van Peursen -- CALAP: An Interdisciplinary Debate between Textual Criticism, Textual History and Computer-Assisted Linguistic Analysis /Konrad D. Jenner , Wida van Peursen and Eep Talstra -- How to Transfer the Research Questions into Linguistic Data Types and Analytical Instruments /Eep Talstra , Konrad D. Jenner and Wida van Peursen -- A Discourse on Method Basic Parameters of Computer-assisted Linguistic Analysis on Word Level /Hendrik Jan Bosman and Constantijn J. Sikkel -- Response to ‘A Discourse on Method’ by Hendrik Jan Bosman and Constantijn J. Sikkel /Pier G. Barbone -- Response to Pier G. Borbone /Hendrik Jan Bosman and Constantijn J. Sikkel -- On not Putting Descartes before D. Hume:Balancing Rationalism and Empiricism in Corpus Tagging. Comments on ‘A Discourse on Method’ by Hendrik Jan Bosman and Constantijn J. Sikkel /A. Dean Forbes -- Response to A. Dean Forbes /Hendrik Jan Bosman and Constantijn J. Sikkel -- Data Preparation: What are we Doing and Why Should we? /Janet W. Dyk -- Response to ‘Data Preparation: What are we Doing and Why Should we?’ by Janet W. Dyk /Geoffrey Khan -- Three Approaches to the Tripartite Nominal Clause in Syriac /Wida van Peursen -- Comments on ‘Three Approaches to the Tripartite Nominal Clause in Syriac’ by Wido van Peursen /Gideon Goldenberg -- Comments on ‘Three Approaches to the Tripartite Nominal Clause in Syriac’ by Wido Van Peursen /Jan Joosten -- A Response to ‘Three Approaches to the Tripartite Nominal Clause in Syriac’ By Wido Van Peursen and a Bit More /Takamitsu Muraoka -- Response to the Responses /Wido van Peursen -- Points of Agreement between the Targum and Peshitta Versions of Kings against the MT: a Sounding /Percy S.F. van Keulen -- A Reply to ‘Points of Agreement between the Targum and Peshitta Versions of Kings against the MT’ by Percy S.F. van Keulen /Bas ter Haar Romen -- Response to ‘Points of Agreement between the Targum and Peshitta Versions of Kings against the MT’ by Percy S.F. van Keulen /Donald M. Walter -- Textual Features of the Peshiṭta of 1 Kings 2:1-9 /Percy S.F. van Keulen -- Worked Examples from 1 Kings 2:1-9 Word Level Analysis /Hendrik Jan Bosman and Constantijn J. Sikkel -- 1 Kings 2:1-9: Some Results of a Structured Hierarchical Approach /Janet W. Dyk -- Lexical Correspondence and Translation Equivalents: Building an Electronic Concordance /Janet W. Dyk -- Nominal Clauses in the Peshiṭta of 1 Kings 2:1-9 /Wido van Peursen -- Exegetical and Text-Historical Differences from the MT in the Peshiṭta Version of 1 Kings 2:1-9 /Percy S.F. van Keulen -- Epilogue: The Peshitta of 1 Kings 2:1-9 from a Linguistic and a Text-Historical Perspective /Wido van Peursen -- Index of passages /P.S.F. van Keulen and W.Th. van Peursen -- Index of authors /P.S.F. van Keulen and W.Th. van Peursen.